Another Road to Serfdom - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2016)
Friedrich Hayek's The Road to Serfdom is an influential book more than seventy years after its publication. This paper examines his arguments and finds that they come up short in many ways and suggests that we have taken “another road to serfdom”. Hayek's mind was completely closed to the possibility that there were multiple threats to individual freedom and not only state power. He failed to see that any concentration of power is dangerous. This was one of his major mistakes. In contrast to Hayek, a public intellectual who warned us of the concentration of power from institutions other than the state was Aldous Huxley who was keenly aware that the danger is not the state per se but rather the concentration of power which might well take on other guises as well. In a 1958 interview he precociously identified Madison Avenue as a potential danger to our autonomy, individuality, and freedom. There are other concentrations of power as well which are just as threatening such as wealthy mega-corporations and billionaire individuals who through their influence on government, on elections, and on the political process are able to change the rules of the market in their favor.
Keywords: B00; 330; Friedrich Hayek